ASSESSMENT OF PATIENT’S KNOWLEDGE ABOUT BLOOD TRANSFUSION AND IMPACT OF STRUCTURED INFORMATION ON THIS KNOWLEDGE: A SINGLE-CENTRE REPORT FROM CENTRAL INDIA - Dr Amrita Tripathi; Dr Devesh Kumar Bulbake; Dr Tamil Priya L; Dr Bhanupriya Mujhalda; Dr Ashok Yadav (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Blood transfusion is a life-saving procedure used in various clinical settings. However, many patients lack adequate knowledge about its indications, benefits, risks, and alternatives. Insufficient understanding can lead to anxiety, reluctance, and non-compliance. Structured educational interventions have been suggested to improve patient awareness and informed decision-making. Objective: This study aimed to assess patients’ baseline knowledge regarding blood transfusion and evaluate the impact of structured educational sessions on their understanding. Material & methods: A descriptive, cross-sectional study was conducted at MGM Medical College and M Y Hospitals, Indore, over six months. A total of 190 patients scheduled for blood transfusion were enrolled after obtaining informed consent. Participants completed a pre-intervention questionnaire (Part-A) assessing their knowledge of transfusion. A structured 30-minute educational session, including visual aids and a Q&A segment, was then administered. Patients subsequently completed a post-intervention questionnaire (Part-B) to evaluate changes in knowledge. Data were analyzed using SPSS 20.0, and statistical significance was determined using paired t-tests and chi-square tests. Results: Before the intervention, only 44.2% of patients knew the reason for their transfusion, 27.4% understood the benefits, and 13.2% were aware of the risks. None of the patients knew about alternative options. After the educational session, knowledge improved significantly (p < 0.001) across all parameters, with 97.3% understanding transfusion indications, 100% recognizing benefits, risks, and alternatives, and 20.5% raising additional questions. Additionally, 90% of patients reported improved understanding, and 85% expressed increased confidence in undergoing transfusion. Conclusion: The study highlights a significant knowledge gap in blood transfusion among patients and demonstrates that structured educational interventions effectively enhance understanding and confidence. Incorporating systematic patient education into routine transfusion care can improve informed consent, reduce anxiety, and promote better healthcare outcomes. Future research should explore long-term knowledge retention and implementation across different healthcare settings.